KETIDAKADILAN GENDER DALAM NOVEL MENIKAH KARYA JANE MARYAM - Ardita Wanda Wiradhana; Tri Indrayanti (Buana Bastra, 2020)
This research is based on the backgaround of the occurrence of gender inequality in the characters in the Merried novel by Jane Maryam, which raises women’s resistance to gaining gender equality. This study aims to describe the farm of gender inequality and resistance in the Merried novel by Jane Maryam. The method in this study uses descriptive qualitative methods. From the analysis of the Merried novel by Jane Maryam conducted, the researchers found the five forms of injustice in the figure, namely in the form of marginalization, stereotyping, subordination, multiple workloads, and violence on the characters. For this form of injustice, there is a form of resistence that demands justice for him. There were three resistance carried out by the figures in Jane Maryam’s married novel, namely resistance to the stereotypes of mixed women, resistance to stereotypes of gender injustice, resistance to violence.